2019
DOI: 10.36348/sjnhc.2019.v02i11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Protocol to Improve Mothers’ Knowledge, Practice and Attitude about Child Abuse

Abstract: Background: Child abuse is a serious problem causing physical, social and psychosocial harm to the children. Aim: To evaluate the effect of educational protocol in improving mothers' knowledge, practice and attitude about child abuse. Design: A quasi-experimental research design [pretest-posttest] was used. Setting: At the out patient's clinics at Zagazig University Hospitals. Sample: A purposive sample consisted of 100 mothers participated in this study and they were chosen according to inclusion criteria. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This result was agreed with El-Said R (2019) who reported that low mothers' knowledge about child abuse before conducting educational sessions were enhanced afterward. (36) Also, Fatouh W et al (2020) declared improvement in mothers' knowledge apropos protecting their children from sexual harassment. (37) In addition, Hima V Krishnan et al (2021) reported that the knowledge of rural mothers concerning child abuse increased after educating them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was agreed with El-Said R (2019) who reported that low mothers' knowledge about child abuse before conducting educational sessions were enhanced afterward. (36) Also, Fatouh W et al (2020) declared improvement in mothers' knowledge apropos protecting their children from sexual harassment. (37) In addition, Hima V Krishnan et al (2021) reported that the knowledge of rural mothers concerning child abuse increased after educating them.…”
Section: Discussionmentioning
confidence: 99%
“…(45) Also, El-Said R (2019) revealed that educational protocol positively changed the mothers' attitudes. (36) Having adequate and accurate information regarding proper child rearing is essential for parents to maintain positive behaviors when dealing with their children. Regarding mothers practices, the results showed that positive parenting practices were commonly used by mothers than other practices pre and post program implementation (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation